Host Exciton Confinement for Enhanced Förster‐Transfer‐Blend Gain Media Yielding Highly Efficient Yellow‐Green Lasers. (1st February 2018) - Zhang, Qi; Liu, Jingguan; Wei, Qi; Guo, Xiangru; Xu, Yan; Xia, Ruidong; Xie, Linghai; Qian, Yan; Sun, Chen; Lüer, Larry; Cabanillas‐Gonzalez, Juan; Bradley, Donal D. C.; et al.
Abstract: This paper reports state‐of‐the‐art fluorene‐based yellow‐green conjugated polymer blend gain media using Förster resonant‐energy‐transfer from novel blue‐emitting hosts to yield low threshold (≤7 kW cm −2 ) lasers operating between 540 and 590 nm. For poly(9, 9‐dioctylfluorene‐ co ‐benzothiadiazole) (F8BT) (15 wt%) blended with the newly synthesized 3, 6‐ bis (2, 7‐di([1, 1′‐biphenyl]‐4‐yl)‐9‐phenyl‐9H‐fluoren‐9‐yl)‐9‐octyl‐9H–carbazole (DBPhFCz) a highly desirable more than four times increase (relative to F8BT) in net optical gain to 90 cm −1 and 34 times reduction in amplified spontaneous emission threshold to 3 µJ cm −2 is achieved. Detailed transient absorption studies confirm effective exciton confinement with consequent diffusion‐limited polaron‐pair generation for DBPhFCz. This delays formation of host photoinduced absorption long enough to enable build‐up of the spectrally overlapped, guest optical gain, and resolves a longstanding issue for conjugated polymer photonics. The comprehensive study further establishes that limiting host conjugation length is a key factor therein, with 9, 9‐dialkylfluorene trimers also suitable hosts for F8BT but not pentamers, heptamers, or polymers. It is additionally demonstrated that the host highest occupied and lowest unoccupied molecular orbitals can be tuned independently from the guest gain properties. This provides the tantalizing prospect of enhanced electron and hole injection and transport without endangering efficient optical gain; a scenario of great interest for electrically pumped amplifiers and lasers. Abstract : Rapid host polaron‐pair formation may compete with stimulated emission from guest molecules in blend gain media. This is shown to be especially problematic for poly(9, 9‐dioctylfluorene‐ co ‐benzothiadiazole) F8BT dispersed in blue polyfluorene hosts. Using hosts with more confined excitons allows sufficient delay for efficient F8BT optical gain to occur and yields high performance yellow‐green lasers.